The Glass Town game - Valente, Catherynne M. 1979- (Margaret K. McElderry Books, an imprint of Simon & Schuster, 2017)
"Inside a small Yorkshire parsonage, Charlotte, Branwell, Emily, and Anne Brontë have invented a game called Glass Town, where their toy soldiers fight Napoleon and no one dies. This make-believe land helps the four escape from a harsh reality: Charlotte and Emily are being sent away to a dangerous boarding school, a school they might not return from. But on this Beastliest Day, the day Anne and Branwell walk their sisters to the train station, something incredible happens: the train whisks them all away to a real Glass Town, and the children trade the moors for a wonderland all their own."--Book jacket flap
Keywords: Brontë family / Juvenile fiction; Brontë family / Fiction; Brontë family; Brothers and sisters / Juvenile fiction; Games / Juvenile fiction; Imagination / Juvenile fiction; Imaginary places / Juvenile fiction; Haworth (England) / Juvenile fiction; Sisters / Fiction; War / Fiction; Fantasy; Brothers and sisters; Games; Imaginary places; Imagination; England / Haworth; JUVENILE FICTION / Action & Adventure; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Fantasy & Magic; War stories; Fantasy fiction; Fiction; Juvenile works; Jugendbuch